Risk attitudes and Medicare Part D enrollment decisions - Stefan Vetter; Florian Heiss; Daniel McFadden; Joachim Winter (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2012)
The new Medicare Part D program provides prescription drug coverage for older Americans through highly subsidized and tightly regulated plans offered by private insurance firms. For most eligible individuals without coverage from other sources, obtaining Part D coverage would be rational, but it requires active enrollment and plan choice decisions. We investigate if non-enrollment in Medicare Part D can partly be explained by risk aversion. Data are taken from a national online survey conducted just after the introduction Part D. The survey included a context-free and a context-related hypothetical lottery to measure an individual's attitude towards risk. Respondents who are risk tolerant according to these measures were significantly less likely to enroll in Part D. We also illustrate that hypothetical choice questions designed to elicit risk attitudes are subject to reference-point effects. Even minor differences in the priming of respondents can result in potentially misleading conclusions about the role of risk aversion in the insurance decisions.
urn:nbn:de:bvb:19-epub-12740-4
Keywords: D03; D81; H51; I1; 330; Risk aversion; Medicare Part D; heterogeneous preferences; insurance demand; survey design; Krankenversicherung; Konsumentenverhalten; Risikopräferenz; Pharmazeutisches Produkt; Alte Menschen; USA